Phosphatase and Tensin Homolog in Non-neoplastic Digestive Disease: More Than Just Tumor Suppressor - He, Tianyu; Zhang, Xiaoyun; Hao, Jianyu; Ding, Shigang (Frontiers in Physiology, 2021)
The Phosphatase and tensin homolog (PTEN) gene is one of the most important tumor suppressor genes, which acts through its unique protein phosphatase and lipid phosphatase activity. PTEN protein is widely distributed and exhibits complex biological functions and regulatory modes. It is involved in the regulation of cell morphology, proliferation, differentiation, adhesion, and migration through a variety of signaling pathways. The role of PTEN in malignant tumors of the digestive system is well documented. Recent studies have indicated that PTEN may be closely related to many other benign processes in digestive organs. Emerging evidence suggests that PTEN is a potential therapeutic target in the context of several non-neoplastic diseases of the digestive tract. The recent discovery of PTEN isoforms is expected to help unravel more biological effects of PTEN in non-neoplastic digestive diseases.